Human response to controlled levels of toluene in six-hour exposures. - Andersen, Ingelise; Lundqvist, Gunnar R; Molhave, L; Pedersen, Ole Find; Proctor, Donald F; Vaeth, M; Wyon, David P (Scandinavian Journal of Work, Environment & Health, 1983)
The nasal mucus flow, lung function, subjective response, and psychometric performance of 16 young healthy subjects was studied during 6-h exposures to clean air and to 10, 40 or 100 ppm of toluene under controlled conditions. The toluene exposures did not affect nasal mucus flow or lung function. At 100 ppm irritation was experienced in the eyes and in the nose. There was a significant deterioration in the perceived air quality and a significant increased odor level during all exposures to toluene. The test battery investigated visual perception, vigilance, psychomotor functions, and higher cortical functions and comprised five-choice, rotary pursuit, screw-plate, Landolt's rings, Bourdon Wiersma, multiplication, sentence comprehension, and word memory tests. In these eight tests measuring 20 parameters, no statistically significant effects of the toluene exposure occurred. For three tests (multiplication errors, Landolt's rings, and the screw plate test) there was a borderline significance (0.05% less than p less than 0.10%). The subjects felt that the tests were more difficult and strenuous during the 100-ppm exposure, for which headache, dizziness, and feeling of intoxication were significantly more often reported. The exposures to 10 and 40 ppm did not result in any adverse effects.